Enterprise Security Architecture - Sherwood, Nicholas (CRC Press, 2005)
Security is too important to be left in the hands of just one department or employee-it's a concern of an entire enterprise. Enterprise Security Architecture shows that having a comprehensive plan requires more than the purchase of security software-it requires a framework for developing and maintaining a system that is proactive. The book is based